KERAPATAN DAN SIFAT MORFOLOGI CIPLUKAN (Physalis sp.) DI GUNUNG KELUD, JAWA TIMUR - Nugraheni Hadiyanti; Pardono .; Supriyadi . (Universitas Islam Kadiri, 2017)
The objectives of the research was to identify the density and morphological character of wild Physalis sp.on some gradients of Mount Kelud, East Java. The research had done using square method with transect (5 plots) in the gradient of Mount Kelud, East Java. The data was collected on 5 stations based on altitude viz.200-400, 400-600, 600-800, 800-1,000 and >1,000 m above sea level. Identification of morphological character was focused on stem, leaf, and fruit covering 20 characters. The research result showed that Physalis sp. in Mount Kelud, East Java had been found at 200 m above sea level and it would lower populations at the higher altitude. Altitude affected to the morphological character of Physalis sp. in Mount Kelud, East Java.